Antibacterial Activity of Genus Bacillus Isolated from Fresh Fruits and Vegetables against Some Foodborne Pathogens - Kawayasakul, Srisuda (Science & Technology Asia, 2020)
Genus Bacillus were isolated from fresh fruits and vegetables and its ability to inhibit the growth of some foodborne pathogens, such as Listeria monocytogenes, Staphylococcus aureus, Bacillus cereus, Salmonella Typhimurium, Escherichia coli and Serratia marcescens was screened an antagonistic capacity using Agar spot assay and Agar well diffusion assay. One hundred and sixty-four isolates of genus Bacillus showed successfully an antibacterial activity. The isolated 16ST4 and 17ST3 revealed a strong inhibition activity against L. monocytogenes at 208.8 and 169.75 AU/ml, respectively. While the best potential against S. Typhimurium was isolated 17ST3 which showed inhibition activity at 146.12 AU/ml. Moreover, CFS of both isolates was stable over a wide temperature range and pH value from 2 to 9. The antibacterial substance was sensitive to all proteolytic enzymes which were properties of protein characteristics. The isolated 16ST4 and 17ST3 were identified by using phenotypic characterization and API 50 CHB indicated that these isolates have high similarity with B. firmus and B. subtilis/amyloliquefaciens, respectively.